Criminal Law Policy Regarding Criminal Sanctions In Law Number 4 Of 2009 As Amended By Law Number 3 Of 2020 Concerning Mineral And Coal Mining And Law Number 32 Of 2009 Concerning Environmental Protection And Management - Dian Anggraini (Sean Institute, 2024)
This study examines the legal implications related to criminal sanctions in Law Number 4 of 2009 concerning Mineral and Coal Mining and other provisions governing environmental protection in Indonesia. The main focus of the study is on the ambiguity of the